Cytotoxic mechanism of Baccharis milleflora (Less.) DC. essential oil. (August 2017) - Pereira, Camila Bugnotto; Kanunfre, Carla Cristine; Farago, Paulo Vitor; Borsato, Débora Maria; Budel, Jane Manfron; de Noronha Sales Maia, Beatriz Helena Lameiro; Campesatto, Eliane Aparecida; Sartoratto, Adilson; Miguel, Marilis Dallarmi; Miguel, Obdulio Gomes
Abstract: The aim of this study was to investigate the cytotoxic activity of the essential oil from cladodes of Bacharis milleflora in relation to Jurkat, Raji and HL-60 cells, as well as exploring the cell mechanisms in order to elucidate how the cytotoxic process occurs. The presence of the following volatile compounds was detected by GC–MS: bicyclogermacrene (12.16%), germacrene D (11.18%), ( E )-caryophyllene (9.28%), and α-humulene (8.05%). In general, IC50 values lower than 50 μg/mL were obtained for all the tumor cells at 24, 48 and 72 h by MTT assay. The decrease in cell DNA content was demonstrated due to the inhibition of the proliferation of Jurkat, Raji and HL-60 cells by B . milleflora essential oil. In particular, Raji cells presented the greatest inhibition of cell proliferation and they were subsequently used to investigate cell death mechanisms. B . milleflora essential oil promoted G0/G1 arrest and also induced cell fragmentation, which was represented by an increase in the sub-G0 population, indicating cell death induced by apoptosis. The selectivity index was 3.97. Necrotic cell death, coupled with low levels of apoptotic cell death, was observed by conventional EB/AO and Hoechst 33342 staining assays, demonstrating that this essential oil acts via both necrotic and apoptotic mechanisms. Highlights: B. milleflora inhibited proliferation of cancer cells by affecting DNA content. B. milleflora presented antitumor mechanism by apoptosis and necrosis. B. milleflora showed reduced cytotoxicity against normal human cells.